Smooth Muscle Contact Drives Endothelial Regeneration by BMPR2-Notch1–Mediated Metabolic and Epigenetic Changes. Issue 2 (18th January 2019) - Miyagawa, Kazuya; Shi, Minyi; Chen, Pin-I; Hennigs, Jan K.; Zhao, Zhixin; Wang, Mouer; Li, Caiyun G.; Saito, Toshie; Taylor, Shalina; Sa, Silin; Cao, Aiqin; Wang, Lingli; et al.
Abstract : Rationale: : Maintaining endothelial cells (EC) as a monolayer in the vessel wall depends on their metabolic state and gene expression profile, features influenced by contact with neighboring cells such as pericytes and smooth muscle cells (SMC). Failure to regenerate a normal EC monolayer in response to injury can result in occlusive neointima formation in diseases such as atherosclerosis and pulmonary arterial hypertension. Objective: : We investigated the nature and functional importance of contact-dependent communication between SMC and EC to maintain EC integrity. Methods and Results: : We found that in SMC and EC contact cocultures, BMPR2 (bone morphogenetic protein receptor 2) is required by both cell types to produce collagen IV to activate ILK (integrin-linked kinase). This enzyme directs p-JNK (phospho-c-Jun N-terminal kinase) to the EC membrane, where it stabilizes presenilin1 and releases N1ICD (Notch1 intracellular domain) to promote EC proliferation. This response is necessary for EC regeneration after carotid artery injury. It is deficient in EC-SMC Bmpr2 double heterozygous mice in association with reduced collagen IV production, decreased N1ICD, and attenuated EC proliferation, but can be rescued by targeting N1ICD to EC. Deletion of EC- Notch1 in transgenic mice worsens hypoxia-induced pulmonary hypertension, in association with impaired EC regenerative function associated with loss of precapillary arteries. We further determined that N1ICD maintains EC proliferative capacity by increasing mitochondrial mass and by inducing the phosphofructokinase PFKFB3 (fructose-2, 6-bisphosphatase 3). Chromatin immunoprecipitation sequencing analyses showed that PFKFB3 is required for citrate-dependent H3K27 acetylation at enhancer sites of genes regulated by the acetyl transferase p300 and by N1ICD or the N1ICD target MYC and necessary for EC proliferation and homeostasis. Conclusions: : Thus, SMC-EC contact is required for activation of Notch1 by BMPR2, to coordinate metabolism with chromatin remodeling of genes that enable EC regeneration, and to maintain monolayer integrity and vascular homeostasis in response to injury. Abstract : Supplemental Digital Content is available in the text.